Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1039/c3tc30684d
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and magnetic properties of one dimensional sandwich polymers: [(Ge5)TM]∞ (TM = Ti, V, Cr, Mn, Fe)

Abstract: The electronic and magnetic properties of a series of one-dimensional carbon-free sandwich polymers [(Ge 5 )TM] N (TM ¼ Ti, V, Cr, Mn, Fe) are examined, based on first principles calculations. Our results show that all of the five polymers are metallic and magnetic. The polymers [(Ge 5 )V] N , [(Ge 5 )Cr] N and [(Ge 5 ) Mn] N exhibit antiferromagnetic behavior, and the other two polymers [(Ge 5 )Ti] N and [(Ge 5 )Fe] N display ferromagnetic spin ordering. It is found that the magnetic moments are mainly contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
(43 reference statements)
0
15
0
Order By: Relevance
“…The germanium element is well-known for its use as semiconductor materials in electronic devices. Because of the high p-type mobility, germanium has been placed under consideration for potential future high-performance electronic transistors . Similar to silicon-based materials, metal-doped germanium materials are believed to bring in improved properties in comparison to the pure ones. In the intensive search for such new materials, several transition metal-doped germanium clusters have been experimentally synthesized and characterized. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The germanium element is well-known for its use as semiconductor materials in electronic devices. Because of the high p-type mobility, germanium has been placed under consideration for potential future high-performance electronic transistors . Similar to silicon-based materials, metal-doped germanium materials are believed to bring in improved properties in comparison to the pure ones. In the intensive search for such new materials, several transition metal-doped germanium clusters have been experimentally synthesized and characterized. …”
Section: Introductionmentioning
confidence: 99%
“…These two states could thus be more populated in the PE experiment, especially the anionic ground state 4 B 1 , and therefore could be taking part in possible electronic transitions underlying bands in the PE spectrum of TiGe 2 − . We predict possible final neutral states in the situation that electronic transitions start from the anionic ground state4 B 1 . If the nearly degenerate state 2 A 1 is significantly populated in a PE experiment, signals of its one-electron ionizations can be observed in the PE spectrum of TiGe 2…”
mentioning
confidence: 99%
“…Ti-doped germanium clusters have attracted much attention because they may be used to produce cluster-assembled materials with special electronic and magnetic properties. 1 In addition, it has been suggested that Ti-Ge binary alloys may be developed for dental materials. 2 And it has been found that strain-released hybrid multilayer Ge-Ti nanomembranes can form anode materials with both high conductivity and high storage capacity, therefore, enhancing the performance of lithium batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and theoretical studies suggested that the doping of transition metals (TMs) can stabilize the cage structures of germanium-based clusters and tailor their properties [1−5]. Ti-doped germanium clusters have attracted much attention because they may be used to produce cluster-assembled materials of special electronic and magnetic properties [6]. It has been proposed that Ti-Ge binary alloys may be developed for dental materials [7].…”
Section: Introductionmentioning
confidence: 99%